2018
DOI: 10.1002/cyto.a.23642
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Apoptotic Circulating Tumor Cells Using in vivo Fluorescence Flow Cytometry

Abstract: Most cancer patients die from metastatic disease as a result of a circulating tumor cell (CTC) spreading from a primary tumor through the blood circulation to distant organs. Many studies have demonstrated the tremendous potential of using CTC counts as prognostic markers of metastatic development and therapeutic efficacy. However, it is only the viable CTCs capable of surviving in the blood circulation that can create distant metastasis. To date, little progress has been made in understanding what proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In this regard, direct detection of CTCs in patients without an invasive procedure is an ideal approach in clinical settings. Nolan et al demonstrated that GFP + CTCs can be directly detected by using in vivo flow cytometry (IVFC) in animal models [ 92 ]. Moreover, the recent development of Cytophone technology (University of Arkansas for Medical Science, AR, USA) shows direct detection of CTCs in patients with melanoma, based on the detection of melanin-bearing CTCs by using an in vivo photoacoustic flow cytometry [ 93 ].…”
Section: Ctc Isolation and Detection Techniquesmentioning
confidence: 99%
“…In this regard, direct detection of CTCs in patients without an invasive procedure is an ideal approach in clinical settings. Nolan et al demonstrated that GFP + CTCs can be directly detected by using in vivo flow cytometry (IVFC) in animal models [ 92 ]. Moreover, the recent development of Cytophone technology (University of Arkansas for Medical Science, AR, USA) shows direct detection of CTCs in patients with melanoma, based on the detection of melanin-bearing CTCs by using an in vivo photoacoustic flow cytometry [ 93 ].…”
Section: Ctc Isolation and Detection Techniquesmentioning
confidence: 99%
“…74 Another study has used IVFC to observe the interactions between circulating breast cancer cells and dendritic cells. Mixed fluorescence and photoacoustic IFVC was also used successfully to detect GFP + breast cancer cells 75 and to identify apoptotic CTC in vivo. After androgen deprivation therapy, patients with prostate cancer were monitored using IVFC, revealing that the therapy reduced CTC count in peripheral blood.…”
Section: In Vivo Flow Cytometrymentioning
confidence: 99%
“…In an effort to detect circulating bacteria cells in the bloodstream of nu/nu mice, we used our custom built in vivo FFC set up, described elsewhere. (25,39) In brief, nu/nu mice are anesthetized using isoflurane and placed on a warmed microscope stage. Mice were anesthetized throughout the entirety of each experiment.…”
Section: Bacteria and Mouse Modelmentioning
confidence: 99%